Sense of place assessment and correlations with the human sensory dimension in Davao City's local cafes - Antatico, Nelson Miles B. (2023)
Cafe?s evolved from a center of social, literary, and political life into spaces for interaction, connection, and secondary work and productivity space. While the modern world influenced the course of the cafe??s evolution, its inherent purpose is still preserved. However, this is slowly changing as cafe?s and their products are being associated with lifestyle and branding, steering off from its essence. To keep up with the fast-paced world, cafe?s adopted multiple strategies like exclusivity, marketing, accessibility, and more, designing their spaces and products to appeal to either specific people or the public. This research leveraged the idea of creating a strong sense of place in local cafe?s through a multi-sensory approach, creating a strong customer base for the cafe? to thrive in. The research employed Qualitative research methods in the form of focus group discussions, and Quantitative research methods through survey questionnaires and spatial assessment to obtain a large dataset. Qualitative data is processed through coding, thematic analysis, and grounded theory, while Quantitative data is analyzed through tallying, Cronbach?s alpha, Pearson correlations, and the Sense of Place Index (SPI). The processed data uncovered a linear correlation between a strong sense of place and the human sensory dimension, and illustrated that a well-accommodated human sensory dimension through architectural and design elements increased the probability of a person?s space attachment and development of sense of place. A set of guidelines was established, specifically formulated to provide a pleasant multi-sensory approach to the patrons about their intent of visit and demographic preferences, ultimately creating a strong community for the local cafe?. The research concluded that aside from specific human sensory dimensions, certain architectural elements and social behavior appear to impact the development of Sense of Place in the cafe?.